Research on the cultivation system of college campus football reserve talents from the perspective of integration of sports and education - Chen, Qiuyi; Chen, Zhijun; Jiang, Bo; Wang, Shaojie (Quality in Sport, 2025)
With the rapid development of football in our country and the country’s increasing emphasis on the training of football talents, establishing an effective environment for the development of talents has become the key to improve the level of campus football. Under this background, the training of college campus football reserve personnel is faced with many challenges, such as the single training mode, the insufficient integration of resources and so on. Starting from the aspects of training concept renewal, curriculum system construction, teacher team construction, site facility guarantee, this study focuses on the construction path of college campus football reserve talent cultivation system from the perspective of sports and education integration. Through the research, it is found that constructing a scientific and reasonable training system is of great significance to improve the quality of college football reserve talents, which not only provides strong support for the development of college football, but also helps to promote the students’ physical and mental health and all-round development, and lays a solid foundation for the long-term development of football cause in our country.